SeneSTEM: promoting STEM in Senegal. Issue Volume 15:Issue S367(2019) (December 2019) - Mbaye, Salma S.; Mbaye, Modou; Kolenberg, Katrien
Abstract: SeneSTEM aims to bring Senegalese children and young people into contact with science, and – by extension – with the STEM disciplines (Science Technology Engineering Mathematics) in a very accessible and illustrative way. We do this with concrete workshops and experiments, for both teachers and for groups of children and young people. In collaboration with different educational organisations in Senegal, among which the Senegalese Association for the Promotion of Astronomy, SeneSTEM ensures that all layers of the population are enthusiastic about science (education). Special attention is given to motivating girls for scientific careers. SeneSTEM actions are based on an international collaboration partly supported by development funds from the city of Antwerp and the University of Antwerp (Belgium).